Analysis of Radiation Barrier Design in Peat Soil Using NCRP Method No.147 at Murjani Regional Hospital - Manik, Jhon Wesly; Hakim, Luqman (International Journal Labs, 2023)
The use of X-ray aircraft can hurt workers and the community, so they must pay attention to radiation protection aspects such as the design of radiation retaining walls which function to absorb and attenuate the resulting radiation exposure. This research was conducted to analyze the value of radiation exposure from radiology buildings on peat soil using the NCRP method No. 147. In this analysis, the rate of radiation exposure was measured using a Gamma Surveymeter, and the Pb thickness was calculated using the fitting and algebraic methods recommended by NCRP No. 147. Measurement and calculation of Pb are divided into 2 areas, namely controlled areas (Point B, Point C, and Point F) and uncontrolled areas (Point A, Point D, Point E, Point G, and Point H). The results of measurements and calculations from these eight protection points obtained radiation exposure rates in controlled areas at Point B (0.09 ?Sv/hour), Point C (0.04 ?Sv/hour), and Point F (0.03 (?Sv/hour ), and the results of calculating Pb thickness at Point B (0.07 mm), Point C (0.03 mm), and Point F (0.18 mm). Meanwhile, the rate of radiation exposure in uncontrolled areas at Point A (0.480 ?Sv /hour), Point D (0.068 ?Sv/hour), Point E (0.075 ?Sv/hour), Point G (0.41 ?Sv/hour), and Point H (0.45 ?Sv/hour), and the results of Pb thickness calculations at Point A (0.46 mm), Point D (0.08 mm), Point E (0.071 mm), Point G (0.038 mm), and Point H (0.005 mm). Based on these results, the radiation exposure rate value in controlled areas is still within safe limits, and in uncontrolled areas, the rate of radiation exposure that occurs is above the threshold of the dose-limiting value set by NCRP No. 147.